The analysis of ostrich chick vitality - Brassó, Dóra Lili; Knop, Renáta; Várszegi, Zsófia; Komlósi, István (Acta Agraria Debreceniensis, 2023)
Examinations on ostrich chick vitality can help to improve the effectiveness of Hungarian ostrich husbandry and hatching technology. The investigations were carried out on an ostrich breeder farm in Eastern Hungary. For the analyses, the Tona et al. (2003) scoring system was applied presenting eight main criteria (activity, feather, condition, eyesight, the condition of navel and leg, the amount of the remaining shell membrane and egg content, and the size and tenderness of the abdomen). Most chicks (98.08%) were vigilant and had clean and dry feathers. There was no difference between the average hatching weights between May and August but a decreasing tendency was shown during the laying season. The vitality total score was above 90 in each evaluated month and was not affected by the hatching month. Our results revealed that the vitality of chicks was not affected by either the hatching month (P=0.51) or the weight category (P=0.11). Neither the hatching weight of chicks and leg condition were correlated (P=0.79). Results showed that the Tona scoring system with small modifications can be well applied to ostrich chicks. Practical on-farm usage of the system can be suggested as an aid in day-old chick evaluation. After individual marking of chicks, the investigation of growth and culling rate could be carried out for more precise conclusions, involving more farms and laying seasons.